Storytelling - Michael Wilson (Arts for health., 2022)
Exploring the potential for storytelling as a creative practice for health and well-being, Michael Wilson considers how the art form might help us reconsider the power relationships in healthcare contexts and restore agency to patients, in partnership with medical professionals. Storytelling is explored not simply as a means of conveying information and experience from one person to another but as an act of listening, a process for thinking, evaluating and understanding. Wilson reflects on his over thirty of years of researching and practising storytelling, and blends his experience with a collection of case studies representing diverse approaches to storytelling for health, including theatre, stand-up comedy, writing, visual arts and digital storytelling. Most importantly, storytelling is approached not from the point of view of the medical practitioner or educator, or even the patient, but through the lens of those who tell stories as a creative and everyday practice. It is a book with the storyteller at its core.